Smoking and school absenteeism among 15- to 16-year-old adolescents - Perelman, Julian (2019)
Background: Schools have a crucial role to play in preventing youth smoking. However, the well-known long-term health consequences of youth smoking may be insufficient to convince education stakeholders to devote efforts to implement school-based programmes. However, if youth smoking were to have short-term consequences, this evidence could prompt education stakeholders' action. In this article, we investigate the link between smoking and school absenteeism. Methods: We used data from the 2011 wave of the European School Survey Project on Alcohol and Other Drugs, on adolescents aged 15-16. We applied logistic models to assess the risk of more than 3 missed school days, by cause, as function of smoking intensity, adjusting for age, sex, socioeconomic status, academic performance, parental involvement and other risk behaviours (alcohol and cannabis consumption). Consistency was assessed by replicating the analyses for each sex and age group and further adjusting for depression and self-esteem. Results: Smoking more than five cigarettes per day was significantly linked to school absenteeism, with a 55% excess risk of missing more than 3 school days per month due to illness (OR = 1.55, 95% CI 1.46-1.64), and a more than two times excess risk due to skipping (OR = 2.29; 95% CI 2.16-2.43). These findings were consistent across age and sex groups. Conclusion: We observed an association between smoking intensity and absenteeism among youth in Europe. This implies that, to the extent that this association is causal, school tobacco control policies may reduce the short-term consequences of smoking on adolescents' education and health.